Supraharmonic mitigation in microgrid and electric vehicle charging station through multilevel converter - Ayyar Subramaniya Siva; Sakunthala Ganesan Ramesh Kumar; Karuppiah Dhayalini (Institute of Advanced Engineering and Science, 2023)
The problem of supraharmonics (SH) in a microgrid (MG) system connected to an electric vehicle (EV) charging station is discussed in this work. SH, or high-frequency harmonics which occur beyond the typical harmonic spectrum, can cause problems with power quality (PQ) and equipment failure. A multilevel converter (MLC)-based solution is proposed together with a frequency domain analysis method to lessen this issue. Using frequency domain methods like the fast fourier transform (FFT), the suggested method precisely measures and examines the SH content in the MG and EV charging station. Based on the findings, an MLC control method that actively lowers the SH is created. The efficiency of the suggested strategy in lowering SH levels and ensuring PQ is assessed through experimental validation. The development of SH analysis and mitigation techniques as a result of this research makes it easier to safely and effectively integrate the infrastructure for EVs with renewable energy sources (RES).